A Thesis Developing Interactive E-Flipbook Module in Teaching Reading Text to the Tenth Grade Students at SMAN 4 Lubuklinggau - Dwi Nur Pajri Syaputra; Ardayati Ardayati; Hamdan Hamdan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Reading is an important skill for students learning English, whether as a second language or a foreign language. Reading still plays a big role and is an essential tool for conveying meaning and information through text. For foreign language learners, reading in English is not an easy task because reading in English is complex and it is difficult to understand the meaning of sentences. Understanding is necessary to understand the meaning and obtain the information conveyed by the author. This happen because the language system of English is different from the students' native language. Hasibuan et al (2021) stated that Reading is an active process, it involves interpreting passages, not just receiving a message. It is reasonable for reading is one of the basic ways of acquiring information. Because when the students have a good competence in reading English, it will help them to obtain and enrich their knowledge.